Durability Judgment of Reinforced Concrete Infrastructures around Butwal Sub-metropolitan City Areas with Corrosion Potential Mapping Method - Thapa Kunwar Magar, Kamal; Paudel, Yuvraj; Gautam, Madhab; Bhattarai, Nootan Prasad; Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2025)
Reinforced concrete is a commonly used construction material in the modern age; however, premature corrosion of the embedded steel poses a significant challenge. This corrosion can lead to the premature deterioration of structures, including buildings, pillars, bridges, and drainage systems. This study evaluates the corrosion risk of fifty-three steel-reinforced concrete infrastructures (S-RCIs) in Butwal Sub-Metropolitan City, Nepal, using the corrosion potential mapping (CPM) technique. The CPM is a non-destructive, cost-effective electrochemical method that complies with ASTM C876-22b standards. It measures in-situ open-circuit potential (OCP) values of the S-RCIs) to qualitatively categorize the probability of corrosion into three levels: low corrosion risk (LCorR, i.e., 90%). The findings indicate that the roof samples of residential buildings predominantly fall into the low-risk category, suggesting satisfactory durability. In contrast, fencing pillars, bridges, and drainage pipes show a high likelihood of corrosion, with OCP values indicating a probability of over 90%. Furthermore, the study emphasizes that structures exhibiting visible cracks, signs of delamination, and prolonged exposure to moisture are significantly more susceptible to reinforcement corrosion.